Demographic Characteristics and Zootechnical Performances of Montbéliarde Dairy Farms in Northern Regions of Cameroon - Kouamo, Justin; Belandi , Abdoulaye Ousmanou; Zangue, Camille Teitsa; Assana, Emmanuel (Universitas Airlangga, 2025)
Background: In Cameroon, the production and consumption of cow milk remain limited, primarily due to inadequate herd management practices, the use of low-performing breeds, and insufficient control of reproductive activities. Purpose: This study aimed to contribute to the improvement of dairy productivity by evaluating the demographic characteristics, reproductive parameters, and milk production performance of Montbéliarde dairy herds in Cameroon. Method: A retrospective cross-sectional survey was conducted from March to May 2022 on nine Montbéliarde dairy farms located in the Adamawa and Far North regions. Data on farm structure, management practices, reproductive performance, and milk yield were collected using structured questionnaires and subsequently analyzed descriptively. Results: The average herd size was 15.00 ± 14.23 cows in Adamawa and 2.25 ± 0.50 cows in the Far North. The mean gestation length, age at first calving, calving interval, lactation duration, and average milk yield were 272.99 ± 8.44 days, 29.89 ± 2.62 months, 14.29 ± 1.11 months, 343.49 ± 17.51 days, and 2513.71± 540.62 L, respectively. Calving, weaning, numerical exploitation, pre-weaning mortality, and overall mortality rates were 27.08%, 47.78%, 61.93%, 42.46%, and 38.91%, respectively. All farms exhibited a negative crude numerical growth rate (-37.18%). Conclusion: The reproductive and productive performances of the Montbéliarde breed in Adamawa and the Far North regions were below expected standards. These suboptimal outcomes are primarily associated with poor management systems and inadequate breeding conditions, emphasizing the necessity for improved herd management, enhanced reproductive monitoring, and targeted interventions to optimize milk production efficiency in Cameroonian dairy systems.